Hubungan Usia dan Pekerjaan terhadap Gangguan Menstruasi pada Akseptor KB Suntik 3 Bulan - Yusmiati, Siti Eka; Susanti, Desy; Ningsih, Nisa Kartika; Riya, Rosa (Universitas Malahayati, 2023)
ABSTRACT Unmet need for contraception can lead to unwanted pregnancies, these pregnancies can increase the risks to the mother, family and society. Unintended pregnancies in developing countries are around 25%. The side effects of using DMPA are menstrual disturbances, weight changes, and dizziness. Menstrual disturbances experienced by DMPA injectable birth control acceptors usually include amenorrhea, menorrhagia, and spotting. To find out the relationship between age and occupation on menstrual disorders in 3-month injection family planning acceptors. Using quantitative research with an analytical survey using a cross sectional approach. The population used is mothers who use 3-month injection birth control in 2022, with a sampling technique using a total sampling of 98 people. The results of data that have been collected are processed both univariate and bivariate data, using chi-square. This study obtained the results that out of 98 respondents, the majority of respondents who experienced menstrual disorder were aged 20-35 years by 66 respondents (67.4%), and the majority of respondents who did not experience menstrual disorder were aged <20 and >35 years by 6 respondents (6.1%), and majority of respondents who experienced menstrual disorders with housewives were 76 respondents (77.6%), and the majority of respondents who did not experience menstrual disorders with housewives were 5 respondents (5.1%). There is a relationship between age (p-value 0.004) and occupation (p-value 0.001) to menstrual disorders in 3-month injection family planning acceptors at Miftahul Jannah midwifery independent practice. The is a relationship between age and occupation on menstrual disorders in 3-month injection family planning acceptors at Miftahul Jannah midwifery independent practice. Keywords : Age, Occupation, 3-Month Injection Family Planning Acceptors ABSTRAK Kebutuhan kontrasepsi yang tidak terpenuhi dapat menyebabkan kehamilan yang tidak diinginkan, kehamilan ini dapat meningkatkan risiko ibu, keluarga, dan sosial. Kehamilan yang tidak diinginkan di negara berkembang sekitar 25%. Efek samping dari penggunaan DMPA adalah gangguan menstruasi,perubahan berat badan, dan pusing. Gangguan menstruasi yang dirasakan pada akseptor KB suntik DMPA biasanya seperti amenorrhea, menoragia, dan spotting. Untuk mengetahui hubungan usia dan pekerjaan terhadap gangguan menstruasi pada akseptor KB suntik 3 bulan (DMPA). Menggunakan penelitian kuantitatif dengan survey analitik menggunakan pendekatan cross sectional. Populasi yang digunakan adalah ibu yang menggunakan KB suntik 3 bulan pada tahun 2022, dengan teknik pengambilan sampel menggunakan total sampling sebanyak 98 orang. Hasil data yang telah dikumpulkan dilakukan pengolahan data baik univariat maupun bivariat, menggunakan chi-square. Penelitian ini diperoleh hasil bahwa dari 98 responden sebagian besar responden mengalami gangguan menstruasi berusia 20-35 tahun sebesar 66 responden (67,4%), dan sebagian besar responden yang tidak mengalami gangguan menstruasi berusia < 20 dan > 35 tahun sebesar 6 responden (6,1%), serta sebagian besar responden mengalami gangguan menstruasi dengan pekerjaan IRT sebesar 76 responden (77,6%), dan sebagian besar responden yang tidak mengalami gangguan menstruasi dengan pekerjaan IRT sebesar 5 responden (5,1%). Terdapat hubungan usia (p-value 0,004) dan pekerjaan (p-value 0,001) terhadap gangguan menstruasi pada akseptor KB suntik 3 bulan di PMB Miftahul Jannah. Terdapat hubungan usia dan pekerjaan terhadap gangguan menstruasi pada akseptor KB suntik 3 bulan di PMB Miftahul Jannah. Kata Kunci: Usia, Pekerjaan, Gangguan Menstruasi